Safeguarding and Child Protection. 0-8 years - Lindon, Jennie; Lindon, Jennie (London : Hodder Education, 2012)
This text provides essential information to ensure high standards for child protection across early years settings, schools and play provision. It covers key legislation and guidance, with clear implications for practice.
Previous ed.: published as Safeguarding children & young people. 2008.
Includes bibliographical references and index.
Keywords: Child welfare -- Great Britain; Society